ETR300 Entrepreneurship. Business Plan : Aneka Kerepek / Roshida Binti Bujang... [et.al] - Bujang, Roshida; Naha, Narazila; Acho, Iraloritha; Nen, Juraidah; Sarkawi, Syarmila (2011)
The name of our company is Aneka Chips. The business is in form of partnership which consists of six members. Each partner contributes certain amount of capital as agreed in agreement. There are no sleeping partners and all are entitled to participate in the business management. We agreed that Roshida Binti Bujang as the General Manager, Ira Loritha Acho as Marketing Manager, Juraidah Binti Nen as the Operational Manager, Narazila Binti Naha as the Administration Manager and Syarmila Binti Sarkawi as the Financial Manager. The selection of General Manager is based on consensus among all the partners and selected based on the experience, skills and ability. The management team will be led by the General Manager and assist by the other managers. The General Manager is responsible in planning, leading, controlling and organizing the business. The Marketing Manager will be responsible to create the marketing plan, identifying the customer’s need and demand, identifying the competitors, target market, market size and forecast the future market. The Operational Manager is responsible to the entire job that related to the operation and will be supervising and coordinating the operation of the business. The Administration Manager is responsible for the job that related to administration such as planning and arranging the remuneration schedule of salary and wages. Lastly, the Financial Manager will be handling the financial matters such as preparing the budget and financial statement for expenses of each departments and controlling the flow of the money of the organization.